Microstructural investigation of Cu/Co multilayer films - Larson, D; Petford-Long, A; Cerezo, A (1999)
Multilayer film structures, with applications based on the giant-magnetoresistance principle, comprise an exciting area of research and have the capability to improve the storage density and sensitivity of devices used by the magnetic recording industry. In order to optimise the performance of these devices, it is imperative to characterise the atomic-level structural and compositional Variations as a function of processing and operating conditions. A new technique, based on focused ion-beam milling, has been developed to fabricate field-ion specimens from nanometer-scale multilayer films deposited directly onto a planar substrate. This method has allowed field-ion microscopy and three-dimensional atom-probe analysis of this type of structure for the first time. A multilayer thin film structure containing 100 repetitions of a (Cu-2nm/Co-2nm) bilayer showed 5-20% Cu alloying in the cobalt layers, a high degree of layer curvature (particularly at grain boundaries) and regions where several cobalt layers appear to be in contact. These observations suggest a degree of ferromagnetic coupling, which explains the relatively high coercivity measurements obtained from the same Cu/Co films. Films which were annealed for 1 h at 360 degrees C showed an increase in grain size, but little change in other microstructural properties. (C) 1999 Elsevier Science S.A. All rights reserved.